Mechanical Performance and Chloride Diffusivity of Cracked RC Specimens Exposed to Freeze-Thaw Cycles and Intermittent Immersion in Seawater - Bei Shen; Yinghua Ye; Bo Diao; Xiaoning Zheng (Advances in Materials Science and Engineering)
The effects of crack width on chloride ingress and mechanical behavior of reinforced concrete (RC) specimens were experimentally studied after exposure to 300 cycles of freeze-thaw and seawater immersion (75 times). Cracks were induced prior to exposure by an eccentric compression load which was sustained until the end of the exposure period. The maximum cracks widths induced in the four column specimens were 0, 0.06, 0.11, and 0.15 mm, respectively. Results show that when the crack width was less than 0.06 mm, the effect of cracks on chloride ingress could be neglected. However, when the crack width was more than 0.11 mm, chloride ingress was accelerated. Results of static loading tests show that both yield load and ultimate load of RC columns decreased as crack width increased. When the crack width was 0.15 mm, yield load and ultimate load of RC column specimen decreased by 17.0% and 18.9%, respectively, compared to a specimen without cracks. It was concluded that crack width significantly promoted local chloride ingress and mechanical performance degradation of RC structures in cold coastal regions or exposed to deicing salts.